Species Turnover across Different Life Stages from Seedlings to Canopy Trees in Swamp Forests of Central Brazil. (6th December 2015) - Fontes, Clarissa G.; Walter, Bruno M. T.; Pinto, José Roberto R.; Damasco, Gabriel
Abstract : Processes driving the assembly of swamp forest communities have been poorly explored. We analyzed natural regeneration and adult tree communities data of a swamp gallery forest in Central Brazil to discuss the role of ecological filters in shaping plant species turnover in a successional gradient. Species data of 120 plots were used to assess species turnover between natural regeneration and adult tree communities. Our analyses were based on 4995 individuals belonging to 72 species. Community patterns were discerned using ordination analyses. A clear floristic turnover among plant life stages was distinguished. Regeneration community of swamp forests was richer in species composition than the adult community. Tree species commonly found in nonflooded gallery forests were present in the regeneration plots but not in the adult community. Differences in the floristic composition of these two strata suggest that not all species in the seedling stage can stand permanent flooding conditions and only a few tolerant species survive to become adult trees. We propose that natural disturbances play an important role by altering limiting resources, allowing seeds of nonflooded forest species to germinate. This paper elucidates the turnover between plant life stages in swamp forests and suggests mechanisms that may shape these communities.